Synthesis of Zeolite-A and Zeolite-Y Using Silica Gel Waste as Silica Source and Modifying with Fe - Khaosomboon, Pornnipa; Khuanmar, Kulyakorn; Weerayutsil, Panomchai (International Journal of Engineering and Technology, 2018)
The purpose of this research was to synthesize zeolite-A (Ze-A) and zeolite-Y (Ze-Y) using silica sources from silica gel waste, and also improving adsorption capacity with Fe which was trapped in the synthesized zeolites:Â Ze-Fe-A and Ze-Fe-Y. All synthesized zeolites were tested with lead solution of 40 mg/L at pH 5. For BET specific surface area, the parent Ze-A and Ze-Y presented surface area of 27.02 and 211.42 m2/g, respectively, whereas Ze-Fe-A and Ze-Fe-Y presented a lower surface area of 10.90 and 28.22 m2/g, respectively. SEM and TEM image demonstrated the cubic and polygon shapes for Ze-A and Ze-Y, respectively, while their modification with Fe presented more round shape. Additionally, both modified zeolites with Fe presented higher adsorption efficiency than their parents. Although the modified zeolites gave lower surface area, the efficiency removal of lead showed higher capacity than zeolite without Fe. It could be concluded that the adsorption mechanism of modified zeolites did not only rely on physical adsorption, but also on chemical adsorption. Â Â Â Â Â